THE IMPACT OF BRAND REPUTATION AND MARKETING TOOLS ON PURCHASING INTENTIONS -CARE PRODUCTS AS AN EXAMPLE - Lin, Linda Lin-Chin; Yang, Ghung-Hsin; Wang, Yan-Ting; Anggarina, Paula Tjatoerwidya; Irawan, Agustinus Purna (International Journal of Application on Economics and Business, 2023)
With air pollution, many dirty particles easily adhere to people's skin, through the function of body care products to complete the daily maintenance work. There are too many body care products on the market, consumers will not buy because of the relationship of brand reputation when purchasing. In addition, counters use different promotional tools to attract consumers to buy, such as providing independent or open skin care and beauty spaces. Will consumers purchase the home's products due to the skin care and beauty services offered by the skin care and beauty space? Therefore, this study uses 2×2 experimental design to analyse the brand reputation of counter body care products and the impact of whether there is an additional skin care and beauty space on consumers' purchase intentions. The results of this study show that consumers will choose high-profile brands to buy skin care products. Moreover, this study confirms that skin care and beauty space settings have an impact on purchase intentions. Therefore, this study suggests that operators can increase brand reputation and provide skin care and beauty spaces to stimulate consumer's willingness to buy.